PERSEPSI MASYARAKAT TERHADAP PENERIMAAN VAKSIN COVID-19 DI PASAR BASAH MANDONGA KENDARI - Rahman Rahman; Akifah Akifah; Lade Albar Kalza (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2022)
As a result of the spread of COVID-19, WHO has encouraged countries to develop a Covid-19 vaccine even though in reality there have been public concerns about the public perception of the aspect of receiving the vaccine itself. Traditional markets are a category of places that are prone to become locations of transmission because of market conditions as public facilities where buying and selling of daily necessities occurs and many people are active in these locations. The purpose of this study was to determine the public's perception of the acceptance of the Covid-19 vaccine in the community group of traders at the Mandonga Wet Market, Kendari City. The type of research used is descriptive. Research results that: People are less enthusiastic/follow the free vaccine program because people are afraid of the impact after vaccination. Information related to the COVID-19 vaccine was obtained from social media and electronic media as well as from the police. Public trust does not fully believe that if you get the vaccine, you can guarantee that you will not be exposed to COVID-19. Vaccine acceptance by the public is influenced by the role of the media which influences negative perceptions, especially on aspects of the post-vaccination effects that result in death. There is a public perception of the government's conspiracy to use the Covid-19 issue to benefit certain groups. Public knowledge is still lacking which results in the ability to make decisions to vaccinate Covid-19. The implication of this research is that all components, including the community, health workers, the government and NGOs, synergize and work together to tackle Covid-19 prevention through the vaccination program.